Combatting corruption in Kazakhstan: A role for ethics commissioners?. (7th November 2019) - Janenova, Saltanat; Knox, Colin
Summary: Central Asian countries have, since gaining independence in 1991, suffered from endemic corruption as a legacy of their Soviet roots. There are multiple ways of tackling corruption ranging from preventative to control measures. One tool in this battery of measures is the use of codes of ethics enforced through ethics commissioners. Kazakhstan is attempting to take a lead role in driving public sector reforms in the Central Asian region but has achieved limited success in addressing the seemingly intractable problem of corruption. This paper offers a formative assessment of the impact of ethics commissioners on the problem. We find limited political commitment for the initiative, institutional weaknesses, and the absence of a problem solving approach by the Kazakhstani government.